Does air quality matter for mutual funds' tracking errors? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Finance at Massey University, Auckland, New Zealand - Roy, Suvra (Massey University, 2019)
Social science literature documents that air quality affects the cognitive dissonance of market participants including retail investors. In this paper, we examine the effect of air pollution on professional investors: mutual fund managers. We find air pollution affects managers’ cognitive performance and behaviour bias, resulting in higher funds’ tracking errors. In addition, we identify factors, which can improve fund managers’ cognitive abilities, reducing the impact of air pollution.
Keywords: Mutual funds; China; Management; Investment advisors; Health and hygiene; Air quality; Health aspects; Cognition; air pollution; tracking error; mutual funds; cognitive biases; managers' behavioural biases; professional investors; 350201 Environment and climate finance